2019
DOI: 10.1038/s41746-019-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact physiological monitoring of preterm infants in the Neonatal Intensive Care Unit

Abstract: The implementation of video-based non-contact technologies to monitor the vital signs of preterm infants in the hospital presents several challenges, such as the detection of the presence or the absence of a patient in the video frame, robustness to changes in lighting conditions, automated identification of suitable time periods and regions of interest from which vital signs can be estimated. We carried out a clinical study to evaluate the accuracy and the proportion of time that heart rate and respiratory ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 77 publications
2
110
0
Order By: Relevance
“…Figure 4 shows the distribution of the time gaps between heart rate estimates from the video camera for the entire dialysis data set. The majority of gaps between the estimates were under 3 min, with the most common gap lasting for 30 s. Although some longer gaps occurred occasionally in the dialysis population, our results are comparable to our previous clinical studies involving the monitoring of vital signs of preterm infants in the Neonatal Intensive Care Unit (NICU) 14 . We reported that the majority of time periods for which heart rate could not be computed in the NICU were less than 30 s.
Figure 4 Gaps in heart rate estimation using the Kalman ND data fusion method.
…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 4 shows the distribution of the time gaps between heart rate estimates from the video camera for the entire dialysis data set. The majority of gaps between the estimates were under 3 min, with the most common gap lasting for 30 s. Although some longer gaps occurred occasionally in the dialysis population, our results are comparable to our previous clinical studies involving the monitoring of vital signs of preterm infants in the Neonatal Intensive Care Unit (NICU) 14 . We reported that the majority of time periods for which heart rate could not be computed in the NICU were less than 30 s.
Figure 4 Gaps in heart rate estimation using the Kalman ND data fusion method.
…”
Section: Discussionsupporting
confidence: 85%
“…Some factors to consider are the quality of the lighting environment available in the hospital ward, the field of view required, the distance at which the camera would be set and the number of patients to be simultaneously monitored from a single camera. If only one patient is required to be monitored at a close distance in a well-lit scenario, such as a camera on top of a neonatal incubator to monitor infants in the NICU 14 , a low-resolution off-the-shelf camera can potentially be used. However, the further the camera is placed from the patient(s), the higher the requirements of the quality of the camera will be.…”
Section: Discussionmentioning
confidence: 99%
“…methods (PCA and ICA blind separation techniques) have been disclosed in [14] based on a similar database having MAE 6.9 BMP and 7.5 BPM values. The [16] describes an implementation of video-based non-contact technologiy to monitor the vital signs of preterm infants. The used dataset is composed of several patients and long recording time.…”
Section: A Nicu Experimentsmentioning
confidence: 99%
“…The involved network was trained by manually annotated skin regions and reached mean absolute error (MAE) 6.9-7.5 breaths per seconds in the collected data set including motion active regions as well. The [15] and [16] demonstrate a complex monitoring system based on a multiple output convolutional neural network. The solution gives a higher level detection capability such as intervention periods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that heart rate can be determined by analyzing skin color changes in video signals. This noncontact and inexpensive method can also be used in certain special scenarios, such as skin damage, neonatal care, and imperceptible monitoring situations [6]- [8]. With the continuous development of noncontact measurement technology, imaging photoplethysmography (PPG)iPPG can provide convenience and comfort and reduce medical costs given that it only requires the processing of body skin color from videos to monitor heart rates automatically by means of data fusion and analysis.…”
Section: Introductionmentioning
confidence: 99%